Recent developments of hydrogen production from sewage sludge by biological and thermochemical process. (26th July 2019) - Liu, Yue; Lin, Ruojue; Man, Yi; Ren, Jingzheng
Abstract: Hydrogen is a kind of clean effective resource. Sewage sludge is regarded as a promising material for hydrogen production because it owns a wide range of sources and the methods are consistent with the goal of sustainable development. This work reviews existing hydrogen production technologies from sewage sludge, including photo-fermentation, dark-fermentation, sequential dark- and photo-fermentation, pyrolysis, gasification, and supercritical water gasification (SCWG). Overall comparison for the involving approaches is conducted based on their inherent features and current development status along with the technical and environmental aspect. Results show that sequential dark- and photo-fermentation and pyrolysis have improved hydrogen yields, but the emissions of carbon dioxide are also remarkable. Biological processes have an advantage in cost, but the reaction rates are inferior to those of thermochemical method. Enhancing methods and improvements are proposed to guide future research on hydrogen production from sewage sludge and promote the effectiveness both technically and economically. Highlights: Principles and features of six sludge-to-hydrogen options were summarized. Comparison was carried out alongside the environmental and technical aspects. Sequential dark/photo-fermentation and pyrolysis show higher hydrogen yields. Methods for improving effectiveness were proposed to guide future research.